ANALISIS BIAYA DAN NILAI TAMBAH USAHA KOPRA DI DESA NAPA KECAMATAN MAWASANGKA KABUPATEN BUTON TENGAH - Erlianti, Rani (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2021)
The purpose of this research was to analyze the costs incurred by farmers in processing coconut into copra and to determine the added value of processing coconut into copra in Napa Village, Mawasangka District, Central Buton Regency. The population in this study were 21copra processors. The sampling in this study was using the census methed where the researchers took the entire copra processing population in Napa Village, Mawasangka District, Central Buton Regency. Data collection tehniques or methods are carried out by circulating a list of questions (questionnaires) to respondents who have been systematically compiled according to research needs. The results showed that, in 1 kg of copra requires 4 coconuts seeds and 1quintal of copra requires 400 coconut seeds, the price of coconut per seed is IDR 1.000 while the price of copra per kg is IDR 5.500 (1) the average total cost of copra proccesing bussiness is IDR 3.222.805 Poduction (2) added value of copra proccesing of Rp 730,19 kg of coconut raw material with the ratio of tambah value obtained of 26,73%. This indicates that the copra business carried out by farmers has a moderate value added ratio.